BLACK’S SELF-RESILIENCE IN MAYA ANGELOU’S POEM STILL I RISE: A MIMETIC ANALYSIS - Aulia, Ela Manikam; Rasiah, Rasiah; Putra, Ansor; Koso, Halijah (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2024)
This research is intended to showcase the reflection of Black self-resilience through Still I Rise poem written by Maya Angelou. Mimetic approach and the concept of self-resilience were used to analyze the problem of this research. Self-resilience was seen in two points; physical and psychological ones. Black self-resilient performed in the poem is considered as the mimetic rendition of the dynamic process of black struggle that leads to the positive adaptations within the context of significant adversity in their life context of the US. Type of this research is included in library research with using descriptive qualitative-interpretive method in analyzing the data. It suggests that Maya Angelou in the poem Still I Rise pictured two kinds of Black self-resilience; physical resilience is showed through some selected words, like; dust, sun, moon, tide, they still arise in their place and time. Black did not and could not be destroyed by the bitter treatment of racism. These words also represented the psychological resilience by adding some other words; having gold mine, walk like I've got oil wells, certainty of tides, and the repeating word, I rise, to show their inner self-motivation, affection, and actualization. This study concluded that Black self-resilience both physically and psychologically reflected by Maya Angelou in her Poem Still I Rise is dealing with the racism. Blacks are destroyed not only physically but also mentality, so, they have to endure themselves by leading to a positive adaptation to exist in the United States.